Institutional support and lecturers’ ICT readiness: Mediating effects of pre-teaching technology use on integration - Maulida Goldy Firdausi; Yosef Budi Susanto; Ringkar Situmorang (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
Information and communication technology (ICT) is considered capable of increasing the effectiveness and quality of learning activities, for example online learning platforms, digital sources and others. Several previous studies have mentioned factors that influence technology integration in learning, namely technological capability, school support and utilization of technology before teaching in class. This study adopts a framework from previous studies with the aim of determining the relationship between lecturers' readiness for technology (ICT capability and self-confidence) and institutional support for technology integration in learning activities and the utilization of technology before teaching as a mediating variable. The research sample was 220 lecturers using non-probability sampling techniques. The results of the study showed that ICT readiness and university support had a direct positive effect on technology integration in classroom learning, and also had an indirect relationship to technology integration mediated by the utilization of ICT before teaching.